PEMBERDAYAAN PEREMPUAN DALAM PEMBANGUNAN BERBASIS PARTISIPASI - Khumaidi Sajuri (MUWAZAH : jurnal kajian gender, 2010)
The process of empowerment of women involves several components but the most responsible and the key is the women themselves. Instruments or other dimensions that are beyond the individual merely as a facilitator and motivator of the process of empowerment of women. In addition, women’s empowerment process also involves the social climate or atmosphere that occurs in society, and environmental conditions within and outside the community who become the object of women’s empowerment. Therefore, the approach made possible the participation of women could participate actively involved in development. The assumption is that knowing the needs of women, resources and problems that exist in women is the women themselves. So women have a very large contribution to development of successfully.